Succesful ageing: ambition and ambivalence - Tesch-Römer, Clemens; Wahl, Hans-Werner; Ayalon, Liat; Rattan, Suresh I. S. (Oxford University Press, 2022)
This book argues that a narrow policy on successful ageing excludes a large portion of ageing individuals from the quest for a good life in old age. It explores various models defining successful ageing and argues that successful ageing in guiding policy will profit by following a pluralistic and holistic view.